Yokukansan Enhances Pentobarbital-Induced Sleep in Socially Isolated Mice: Possible Involvement of GABAA - Benzodiazepine Receptor Complex - Nobuaki Egashira; Ai Nogami; Katsunori Iwasaki; Ayumi Ishibashi; Naoki Uchida; Kotaro Takasaki; Kenichi Mishima; Ryoji Nishimura; Ryozo Oishi; Michihiro Fujiwara (Elsevier, 2011)
Abstract.: In the present study, we investigated the effect of the Kampo medicine Yokukansan (YKS) on pentobarbital-induced sleep in group-housed and socially isolated mice. Socially isolated mice showed shorter sleeping time than the group-housed mice. YKS (300 mg/kg, p.o.) prolonged the pentobarbital-induced sleeping time in socially isolated mice without affecting pentobarbital sleep in group-housed mice. The prolongation of sleeping time by YKS was reversed by bicuculline (3 mg/kg, i.p.) and flumazenil (3 mg/kg, i.p.), but not WAY100635. These findings suggest that the GABAA - benzodiazepine receptor complex, but not 5-HT1A receptors, is involved in the reversal effect of YKS on the decrease of pentobarbital sleep by social isolation. Keywords:: sleep, social isolation, Yokukansan